L'estetica negli scritti giovanili di Simone Weil (Materiali di Estetica. Terza serie, 2017)
This paper focuses on an early essay by Simone Weil on aesthetics. This work, entitled The Beauty and the Good and dating back to February 1926, was composed by the author when she was still a student in high school, and it is the first document in which the future philosopher deals with problems concerning aesthetics, with intuitions and arguments that we will find expanded and developed in the major works. And yet this writing, due to the problematic nature that pervades it, cannot be read as a mere anticipation of Weil’s further reflection, but needs a specific analysis for the richness of the content in itself.  Through a reflection on the sublation of the material aspects of the work of art, Weil attempts to elaborate the dimensions through which an artifact can become an aesthetic object. A further intuition of the philosopher sketches the possible relationship between work of art and time, and the possibility, for the work of art, to overcome its specific space-time collocation and rise to an eternal dimension, to a sort of «absolute» in the flow of current time.